RE-DESIGN SISTEM KEMUDI KENDARAAN BIO-HYBRID OBHI-MEC UNUD DENGAN MENGGUNAKAN SINGLE STEERING JOINT - Adiansyah, Anugrah Putra; Karohika, I Made Gatot; Widiyarta, I Made (Teknik Desain Mekanika, 2024)
Abstract The steering system is a mechanism on a vehicle that is useful for controlling and changing the direction of the wheels. Changing the direction of movement of the wheels is done by turning the two front wheels of the vehicle. Currently, the OBHIMec biohybrid car uses a manual steering system with a simple tie rod mechanism, which can support the load when the vehicle is movingThis research aims to examine the effect of load on rotational force in the steering design of Unud's obhimec biohybrid vehicle. This research was carried out by comparing two steering system models, namely the current steering model with two steering joints and a modification with one steering joint.The results of testing using a single steering joint steering system succeeded in reducing effort when changing steering direction, where the torque on the steering wheel and the force required when turning the wheel were reduced on average by 33% compared to using double steering joint steering, so that the single steering joint produces lighter and easier steering when driving the Obhi-Mec Unud Bio-Hybrid vehicle.. Keywords: system steering joint , force, moment